SCREENING OF POTENTIAL PROBIOTIC LACTOBACILLUS STRAINS ISOLATED FROM FERMENTED FOODS, FRUITS AND OF HUMAN ORIGIN - SADRANI, HEMAL; DAVE, JAYANTILAL; BHARATKUMAR RAJIV MANUEL VYAS (Asian Journal of Pharmaceutical and Clinical Research, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> Objective: To screen and characterize Lactobacillus strains having potential probiotic properties from fermented foods and fruits, and to investigate cell surface characteristics and antimicrobial activity against food-borne and gastrointestinal tract (GIT) pathogens. Methods and Results: In the present study, twenty five Lactobacillus strains were isolated from fruits, fermented foods and human origin on De Man Rogosa and Sharpe (MRS) agar plates and identified on the basis of their phenotypic characteristics and 16s rDNA sequencing. Isolated Lactobacillus strains tolerated inhibitory substances like bile (upto 4%), NaCl (upto 8%), phenol (upto 0.6%) and low pH (2.0). Six of the isolates exhibited inhibitory activity against food-borne and GIT pathogens by well diffusion method. The isolates appeared to possess hydrophilic cell surface as determined by microbial adhesion to n-hexadecane. Isolates auto-aggregated and also co-aggragated with pathogens tested. The isolates were not susceptible to antibiotics like vancomycin, tobramycin, kanamycin and norfloxacin while were highly susceptible to chloramphenicol, clindamycin, erythromycin, oleandomycin and penicillin G. None of the isolates showed haemolytic activity. Conclusion: Six strains (Lactobacillus paracasei HML1, L. paracasei CR7, L. plantarum BRMV1, L. plantarum F1 and L. plantarum OC6) showed potential probiotic properties as well as strong in vitro antibacterial activity against various food-borne and gastrointestinal tract (GIT) pathogens.Â Keywords: Antimicrobial activity, Lactobacillus, Acid tolerance, Bile tolerance, Hydrophobicity, Probiotics Â <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>